FAKTOR-FAKTOR PELAPORAN KEUANGAN BERBASIS WEBSITE DENGAN MODEL REGRESI LOGISTIK - Ginting, Wenny Anggeresia; Munawarah, Munawarah -; Dini, Siti (Universitas Medan Area, 2019)
This study shows the empirical evidence whether there are influences on company size, profitability, and auditor reputation on the disclosure of website-based financial reporting and also those not based on company websites in 2016. This study uses data from all non-financial companies listed on the Indonesia Stock Exchange (IDX) 2016. The testing of research data using logistic regression analysis. The results showed that partially the profitability variable, type of company, and auditor reputation had significant and significant effect on IFR (Internet Financial Reporting), while the firm size variable did not affect non-financial companies listed on the Indonesia Stock Exchange. Opportunities for non-financial companies that implement IFR are greater than companies that do not implement IFR, this reason supports that the existence of the internet through IFR has been widely used to expand business networks in each business entity through the company's website compared to companies that have not implemented it.